2020
DOI: 10.1088/1674-1056/ab8216
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid linear amplifier-involved detection for continuous variable quantum key distribution with thermal states*

Abstract: Continuous-variable quantum key distribution (CVQKD) can be integrated with thermal states for short-distance wireless quantum communications. However, its performance is usually restricted with the practical thermal noise. We propose a method to improve the security threshold of thermal-state (TS) CVQKD by employing a heralded hybrid linear amplifier (HLA) at the receiver. We find the effect of thermal noise on the HLA-involved scheme in near-and-mid infrared band or terahertz band for direct and reverse reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Because optical quantum repeaters are expected to become commercially accessible soon, QKD networks are now developed entirely using the Trusted Repeater Approach (TRA) [26]. Numerical simulations demonstrated that inserting HLA (hybrid linear amplifier) before Bob's detector can improve TS-CVQKD (thermal-state continuous-variable quantum key distribution) protection in the near-and mid-infrared or terahertz regions [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because optical quantum repeaters are expected to become commercially accessible soon, QKD networks are now developed entirely using the Trusted Repeater Approach (TRA) [26]. Numerical simulations demonstrated that inserting HLA (hybrid linear amplifier) before Bob's detector can improve TS-CVQKD (thermal-state continuous-variable quantum key distribution) protection in the near-and mid-infrared or terahertz regions [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They endow quantum computing with absolute security. With this advantage, a huge number of quantum cryptography protocols have been proposed to solve cryptography challenges, embracing quantum secure direct communication (QSDC), [5][6][7][8] quantum secret sharing (QSS), [9][10][11][12] and quantum key distribution (QKD), [13][14][15][16][17] as well as quantum secure multiparty computation (QSMPC), [18][19][20][21][22][23][24] etc.…”
Section: Introductionmentioning
confidence: 99%
“…This makes the application of short-range quantum cryptography possible, and the study of thermal-state CV-QKD becomes very important. In recent literature, the theoretical and experimental security of different detection and reconciliation modes of thermal-state CV-QKD has been proved [19], [31]- [35].…”
Section: Introductionmentioning
confidence: 99%